A randomised dose finding study of oral tacrolimus (FK506) therapy in refractory ulcerative colitis. Issue 9 (16th February 2006) - Ogata, H; Matsui, T; Nakamura, M; Iida, M; Takazoe, M; Suzuki, Y; Hibi, T
Abstract : Background and aims: Immunosuppressive therapy with intravenous ciclosporin is an alternative treatment option to total colectomy for patients with ulcerative colitis (UC), while the benefits of oral administration of tacrolimus are not well defined and are based on reports of several uncontrolled studies. Methods: Patients with refractory active UC were randomly assigned to a high trough concentration (10–15 ng/ml) group (HT group) (n = 21), low trough concentration (5–10 ng/ml) group (LT group) (n = 22), or placebo group (n = 20). Patients received an initial oral dose of 0.05 mg/kg tacrolimus or placebo twice daily. Efficacy was evaluated in 60 patients based on a disease activity index (DAI) score. Fifty eight patients had additional treatment with tacrolimus and were evaluated for efficacy in a 10 week open label extension. Results: An improvement in DAI score (⩾4 points, all categories improved) was observed for 68.4% of cases in the HT group compared with 10.0% in the placebo group (p<0.001). In the HT group, 20.0% of patients had clinical remission and 78.9% had mucosal healing. In the open label extension, 55.2% of all patients had an improved DAI score at week 10. Mean dose of prednisolone was reduced from 19.7 mg/day at study entry to 7.8 mg/day at week 10. The incidence of side effects in the HT group was significantly higher than that of the placebo group (p = 0.043). The most common event was mild finger tremor. Conclusions: Our findings demonstrate dose dependent efficacy and safety of oral tacrolimus for remission-induction therapy of refractory UC. The optimal target range appears to be 10–15 ng/ml in terms of efficacy with two week therapy.